Using student voice to examine teacher practices at a cyber charter high school. (19th December 2016) - Borup, Jered; Stevens, Mark A.
Abstract: Efforts to identify K‐12 online instructional best practices and standards have been limited because they largely ignored students' voice—the primary stakeholder in any educational context. In this case study, we conducted 20 interviews among 10 students enrolled in a cyber charter high school. Qualitative analysis of interviews found that students valued teachers' efforts to nurture caring relationships, facilitate sustained dialogue, design and organize engaging learning activities, and provide personalized instruction. However, students found that teachers varied in their abilities to effectively perform these activities and provided recommendations to improve how courses were designed and how teachers interacted with students. Although findings from this case study should not be generalized, these findings may prove insightful to those in similar contexts. Research should continue to obtain and understand online students' voices and assist cyber schools as they work to respond to students' needs.